PROSPEK KAYU KUALITAS RENDAH DAN KURANG DIKENAL SEBAGAI SUBSTITUSI KAYU KOMERSIAL - Arsad, Effendi (Kementerian Perindustrian, 2013)
At this time the wood with a high quality hard to find and expensive. There for, construction of residential buildings began to use other types of low-quality wood strong. The use of raw materials to make buildings less good quality. It causes no long lasting building, susceptible organisms such as termites and other destructive. In order to bequalified building efforts are needed to improve the quality of the raw material of low quality wood strong, with a variety of technical. Strong improvement in the quality of low quality wood can be done in many ways, including preservation using chemicals such as by way of soaking and boiling in a solution of Sodium Hydroxide (NaOH), CCB, CCF and itc. Performed with the compression heat. Strong low quality wood species used is lua timber, lumber and wood tarap flowers, pressure felts give better results than treatment at others. Three types of wood used is solid wood class III - V increased the flower timber strength class III, wood tarap class V, wood durin class III, solid wood lua IV and wood kelampayan IV while the wood all is showed no improvement.Keywords: wood non commercial, physical, mechanical, preservation